Fundamentals of energy storage from first principles simulations: Challenges and opportunities - Kowalski, Piotr M.; Bornhake, Thomas; Cheong, Oskar; Dohrmann, Noah; Koch Liston, Andre Luiz; Potts, Shannon Kimberly; Shad, Alison; Tesch, Rebekka; Ting, Yin-Ying (Frontiers in Energy Research, 2023)
Efficient electrochemical energy storage and conversion requires high performance electrodes, electrolyte or catalysts materials. In this contribution we discuss the simulation-based effort made by Institute of Energy and Climate Research at Forschungszentrum Jülich (IEK-13) and partner institutions aimed at improvement of computational methodologies and providing molecular level understanding of energy materials. We focus on discussing correct computation of the electronic structure, oxidation states and related redox reactions, phase transformation in doped oxides and challenges in the computation of surface chemical reactions on oxides and metal surfaces in the presence of electrolyte. Particularly, in the scope of this contribution we present new simulated data on Ni/Co and Am/U-bearing oxides, and Pb, Au and Ag metal surface materials. The computed results are combined with the available experimental data for thoughtful analysis of the computational methods performance.